2017
DOI: 10.47469/jees.2017.v03.100033
|View full text |Cite
|
Sign up to set email alerts
|

Flexirubin-type Pigment Production from Chryseobacterium artocarpi CECT 8497 and its Application as Natural In

Abstract: Interest and demand for bacterial pigments is growing due to rising awareness of toxicity of synthetic dyes. This study evaluated on the production of flexirubin-type pigment from Chryseobacterium artocarpi CECT 8497 using liquid pineapple waste in 5-L bioreactor and its application as environmental-friendly ink. Liquid pineapple waste supported bacterial growth and pigment production for C. artocarpi CECT 8497. The ink was successfully formulated with polyvinyl butyral and polyvinyl pyrrolidone giving a smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…Values for Chroma (saturation) and Hue angle were calculated as 33.2 ± 3.9 and 83.2 ± 1.9, respectively. Likewise, previous studies on the colorimetric parameters of flexirubintype pigments extracted from Chryseobacterium strains also revealed positive b* values and Hue angle values close to 80°, which represent colors in the yellow/orange region [31,32].…”
Section: Characterization Of the Pigment Extractsupporting
confidence: 61%
See 1 more Smart Citation
“…Values for Chroma (saturation) and Hue angle were calculated as 33.2 ± 3.9 and 83.2 ± 1.9, respectively. Likewise, previous studies on the colorimetric parameters of flexirubintype pigments extracted from Chryseobacterium strains also revealed positive b* values and Hue angle values close to 80°, which represent colors in the yellow/orange region [31,32].…”
Section: Characterization Of the Pigment Extractsupporting
confidence: 61%
“…The antioxidant activity of flexirubins can be attributed to the hydrogen atom transfer from the phenolic hydroxyl group and the long polyene chain, as previously determined through different assays [42]. Moreover, flexirubin pigments produced by Chryseobacterium strains are very stable under UV and sunlight exposure even at high temperatures [32,40], suggesting the importance of these pigments for a broad range of applications. In this regard, polymeric nanofibers incorporating flexirubin showed ABTS radical scavenging activity and the ability to reduce enzymatic browning of apple slices.…”
Section: Antioxidant Activitysupporting
confidence: 58%
“…Fewer studies were conducted on flexirubin pigment compared to other yellow pigments, thus reducing its marketability rate. However, existing studies have demonstrated that flexirubin pigment from C.artocarpi can be used as a natural ink, antioxidant, and anticancer agents [1][2][3].…”
Section: Introductionmentioning
confidence: 99%